Description of the Sense of Community in Regional Leadership Members of the East Java Ikatan Pelajar Muhammadiyah : Gambaran Sense of Community pada Pengurus Pimpinan Wilayah Ikatan Pelajar Muhammadiyah Jawa Timur - Rahmawati, Axnes Tasya; Mariyati, Lely Ika (Journal of Islamic and Muhammadiyah Studies, 2024)
This study investigates the relationship between sense of community and performance among members of the Muhammadiyah Student Association in East Java. Employing a descriptive quantitative research method, data were collected from a population of 65 individuals using saturated sampling. Research instruments, derived from previous studies, demonstrated satisfactory validity and reliability. Results reveal a predominantly high sense of community among members, with 9.20% categorized as very high, 21.50% as high, 43.20% as medium, 20% as low, and 6.10% as very low. These findings underscore the importance of fostering a strong sense of community within groups, as it positively impacts individual and collective performance, thus offering valuable insights for community development and organizational management. Highlights: Importance of sense of community: Emphasizes the role of community cohesion in driving individual and collective performance. Research methodology: Descriptive quantitative approach provides an overview of sense of community among members. Findings: Majority of members exhibit high to very high sense of community, highlighting strong group cohesion within the Muhammadiyah Student Association in East Java. Keywords: Community, Sense of Community, Ikatan Pelajar Muhammadiyah